Interpretation of Constitution in Indonesia: Orisinalism, Non-Orisinalism, or Explicism - Haryono, Dodi (International Journal of Psychosocial Rehabilitation, 2020)
In Indonesia, the originalism and non-originalism approaches in interpreting the constitution are used by the Constitutional Court of the Republic of Indonesia without having to be distinguished. This can be justified both theoretically, practically, and juridically in Indonesia. It’s just that the use of such a mixed approach contains its own strengths and weaknesses. This article explains and analyzes the use of various methods of interpreting the constitution, especially in the practice of constitutional justice in Indonesia. Then explain and put forward the idea of developing a method of interpreting the constitution that is unique to Indonesia. In the end, this article recommends that the interpretation of eclecticism as applied by the Indonesian constitutional court is worthy of continuing development. Nevertheless, its use should be carried out holistically, integratively, and dynamically, linking it with the ideology of Pancasila as the basis of the Indonesian state